The practice and innovation of compatible marine utilization models in China - Li, Yanping; Yang, Yan; Hou, Yuting; Liu, Xiao; Liu, Dahai (Frontiers in Marine Science, 2024)
Marine Spatial Planning (MSP) is essential for optimizing marine resources allocation and resolving conflicts in sea use, but it is challenged by the complex and multi-functional nature of maritime resources. This study utilizes participatory methods, inductive reasoning, and overlay analysis to explore both theoretical and practical aspects of compatible marine utilization models. The paper begins by clarifying the logic of compatible sea use through marine functional zoning and identifying its core characteristics: quantity, spatial conflict, and impacts on natural attributes. Building on China’s national territorial spatial planning reforms and practical experiences, the paper introduces three major categories of compatible marine use models: development sequencing compatibility, spatial coexistence compatibility, and functional synergy compatibility. A compatibility discrimination matrix is developed to assess these models across different marine functional areas. Combined with the compatibility discrimination results, taking the marine and coastal spatial planning of Yantai City in China as a case study, the paper analyzes the compatibility demands and planning strategies within various marine functional areas. Finally, it evaluates the risks associated with each compatibility model and proposes targeted control strategies tailored to the specific features of each model and characteristics of sea use activities. The research findings highlight the positive role of compatible sea use models in promoting marine economic development, enhancing spatial efficiency, and mitigating sea use conflicts. However, these models also present varying potential risks, necessitating differentiated control strategies aligned with legal frameworks and specific sea use activities. The study offers valuable insights for MSP and contributes to the efficient utilization of marine resources and the advancement of marine spatial governance.